Association Between Dimension of Intelligence and Work Performance among Medical Data Recorders: A Cross-sectional Study - Faida, Eka Wilda; Wijayanti Sutha, Diah; Aisatus Saadah, Alfina (The Indonesian Institute of Science and Technology Research, 2025)
Medical records are vital for informed diagnosis and patient care. Therefore, optimizing the performance of medical data recorders is essential. Performance can be assessed based on several factors, including ability, attitude, appearance, leadership support, initiative, and responsibility. Intelligence, encompassing intellectual, emotional, and spiritual dimensions, represents an important aspect of ability. This study examines the relationship between work performance and intelligence dimensions among medical data recorders. A cross-sectional study was conducted at the Health Center of East Surabaya with 35 participants. Data were analyzed using multiple linear regression. Most participants were aged 30–40 years, predominantly female, held a diploma, and had over five years of work experience. The highest mean intelligence score was observed for spiritual intelligence (mean = 4.37), specifically in flexibility and the principle of truth. The highest mean performance score was observed for concentration (mean = 4.54). Linear regression analysis indicated that gender and intelligence dimensions significantly influenced performance, with a strong correlation (R = 0.767). These findings highlight the importance of structured leadership coaching, memory enhancement modules, and emotional resilience training for health workers to improve performance.